(untitled) (Research, Society and Development, 2020)
The present work aimed to analyze the scientific studies that describe the systematization of the applicability of the Lean methodology in the organization of health services. It is an integrative review of articles published in Portuguese, English or Spanish, available in full in the databases PUBMED, CINAHL, EMBASE e LILACS, MEDLINE, The descriptors was used “Leanmethodology”; “Leanhealthcare”; “healthservice”; “organizations”; “administration” and keywords with the boolean “AND” and “OR”, respectively, nine studies were selected and analyzed. The analysis of the selected manuscripts made it possible to elaborate a category Applicability of the Lean methodology in health services / processes: objectives and improvement project teams. It is concluded that the application of the Lean methodology does not offer only a specific result, it can go beyond what is desired to be achieved with the objectives previously and outlined, since health services are organized, created or restructured in a standardized manner, with a trained staff, aiming to identify and eliminate residues, waste and avoid rework.